Management of acute bronchiolitis: can evidence based guidelines alter clinical practice?. Issue 12 (22nd August 2008) - Barben, J; Kuehni, C E; Trachsel, D; Hammer, J
Abstract : Background: Acute bronchiolitis is the most common lower respiratory tract infection in infants and there is no evidence that drug treatment alters its natural course. Despite this, most Swiss paediatricians reported in 2001 prescribing bronchodilators and inhaled corticosteroids (ICS). This situation led to the creation of national guidelines followed by a tailored implementation programme. The aim of this study was to examine if treatment practices changed after the implementation of the new guidelines. Methods: A questionnaire on treatment of bronchiolitis was sent to all Swiss paediatricians before (2001) and after (2006) creation and implementation of national guidelines (2003–2005). Guidelines were created in collaboration with all paediatric pulmonologists and implemented carefully using a multifaceted approach. Results: Questionnaires were returned by 541 paediatricians (58%) in 2001 and by 639 (54%) in 2006. While both surveys showed a wide variation in the treatment of bronchiolitis between physicians, reported drug prescription decreased significantly between the two surveys. For outpatients, general use (for all patients) of bronchodilators dropped from 60% to 23%, and general use of ICS from 34% to 6%. For inpatients, general use of bronchodilators and ICS dropped from 55% to 18% and from 26% to 6%, respectively (all p<0.001). The decrease was evident in all regions, among hospital and primary care physicians, and among general paediatricians and paediatric pulmonologists. Conclusions: National guidelines together with a tailored implementation programme can have a major impact on medical management practices in a country.